Construction of gradient hierarchical and hetero-interfaces structure for ultra-broad microwave absorption - Chunwei Lei; Jian Li; Yuhan Wu; Yu Xie; Yun Ling; Juhua Luo (Nano Materials Science)
Currently, carbon materials derived from biomass are widely sought after as electromagnetic absorbing(EMWA) materials owing to the unique structure, as well as the wide range of natural acquisition pathways, economic viability, and simple processing. However, due to the high dielectric properties, mismatched impedance and single attenuation mechanism, they cannot achieve efficient EMWA performance. Herein, the biomass carbon/Co/porous carbon magnetic composites with a layered gradient structure were fabricated by in-situ deposition of ZIF-67 on the lotus leaf base and then pyrolysis at high temperature. By adjusting the pyrolysis temperature, the sample obtained at 650 ​°C achieved a minimum reflection value (RLmin) of −34.2 ​dB at a matching thickness of 2.6 ​mm, and a maximum effective absorption bandwidth (EAB) of 7.12 ​GHz. The results indicate that this magnetic composite with a multi-sized layered gradient porous structure has a good electron transport network, a large number of heterogeneous interfaces, and dipole polarization centers, which are conducive to multiple reflection and scattering of microwaves, conduction loss, interface loss, magnetic loss, and impedance matching of materials. Therefore, this work provided a reference for optimizing the EMWA performance of carbon materials and designing a layered gradient porous magnetic composite with multi-sized structure.